The association between hepatitis C virus infection and renal function. Issue 8 (1st June 2021) - Gantumur, Gantsetseg; Batsaikhan, Batbold; Huang, Ching-I; Yeh, Ming-Lun; Huang, Chung-Feng; Lin, Yi-Hung; Lin, Tzu-Chun; Liang, Po-Cheng; Liu, Ta-Wei; Lee, Jia-Jung; Lin, Yi-Ching; Lin, I-Ling; et al.
Abstract : Background: The association between hepatitis C virus (HCV) infection and chronic kidney disease (CKD) still remains controversial. We aimed to investigate whether HCV really affects renal function, and to analyze the association between clinical effects of CHC and decreased kidney function (assessed by glomerular filtration rate (eGFR) level). Methods: An estimated 3360 patients with HCV infection and 3360 age- and sex-matched community-based control individuals without HCV were enrolled (1:1, case and control ratio) in this study between 2004 and 2016. We used the modification of diet in renal diseases to calculate eGFR. Demographic and laboratory parameters were assessed, and appropriate statistical methods were performed for the analysis. Results: Multivariate logistic regression analysis revealed that serum alanine aminotransferase level (odds ratio [OR] 0.998; 95% confidence interval [CI] 0.997–0.999; P = 0.001), platelet count (OR 0.997; 95% CI 0.995-0.999; p = 0.002), and hypertension (OR 1.31; 95% CI 1.03-1.66; P = 0.027) were significantly associated with HCV infection and serum triglyceride levels (OR 1.001; 95% CI 1.00-1.002; p = 0.005), platelet count (OR 0.996; 95% CI 0.995-0.997; p < 0.001), body mass index (BMI) >25 (OR 1.43; 95% CI 1.23-1.67; p < 0.001), hypertension (OR 1.69; 95% CI 1.42-1.99; p < 0.001), hyperlipidemia (OR 1.32; 95% CI 1.02-1.71; p = 0.035), and diabetes (OR 1.33; 95% CI 1.03-1.71; p = 0.032) were significantly associated with a low eGFR (<90 mL/min/m 3 ) in control subjects. The BMI >25 kg/m 2, hypertension, and diabetes were found to be associated with low eGFR interaction with the HCV infection, via a multivariate analysis. Conclusion: Our study found that the patients with HCV infection are associated with a low eGFR compared with non-HCV–infected patients. This association is consistent in obese, diabetic, and hypertensive patients.